DIGITAL DOPAMINE: IMPACT OF SOCIAL MEDIA USE ON THE REWARD SYSTEM AND VULNERABILITY TO ADHD AND ANXIETY IN YOUNG PEOPLE (CIPEEX, 2025)
INTRODUCTION: With the new digital age, social media access has become an addiction and a routine part of today's young people's lives. However, this intense use of technology has been associated with behavioral changes. Therefore, this technological hyperstimulation constitutes a possible link between "digital dopamine" and vulnerability to ADHD and anxiety disorders. OBJECTIVE: To highlight the impact of excessive social media use on the dopaminergic reward system and its relationship with ADHD and anxiety symptoms in young people. METHODOLOGY: The systematic review was conducted taking into account the PICo strategy. PubMed, BVS, and Scielo databases were used, using the Health Science Descriptors "dopamine," "reward system," "social media," "ADHD," and "anxiety," using the Borlean operator AND. Five articles published in the last five years were selected and available in full online. RESULTS: After analyzing the studies, it was possible to conclude, based on functional neurological imaging, that intense digital stimulation has the direct ability to modulate the dopaminergic reward system, as it increases activation of the nucleus accumbens and the ventromedial prefrontal cortex, similar to patterns observed in addictive behaviors. Furthermore, research has shown that those who use social media for more than four hours per day show an average increase of 30% in symptoms of inattention and 25% in impulsivity, in addition to high GAD-7 and ASRS-18 scores. Thus, it is possible to observe the direct impact of social media on the lives of young people. CONCLUSION: Therefore, the concept of "digital dopamine" allows us to understand how social media modulate the reward system and impact mental health, increasing symptoms of ADHD and anxiety in this group. Understanding this phenomenon is essential for guiding prevention and mental health interventions for young people in the digital age.
Keywords: anxiety; dopamine; ADHD; Social Networks; Reward System